EMPAGLIFLOZIN IS MORE EFFECTIVE IN REDUCING MICROALBUMINURIA AND ALT LEVELS COMPARED WITH DAPAGLIFLOZIN: REAL LIFE EXPERIENCE - ÜSTAY, ÖZLEM (EDITURA ACAD ROMANE, 2020)
Context. Sodium Glucose Co-Transporter-2 inhibitors (SGLT2i) are oral antidiabetic agents that can be used with insulin in the treatment of type 2 diabetes mellitus, known for cardiovascular and renal benefits. Dapagliflozin and empagliflozin are available in Turkey and we aimed to evaluate real-life data of using these two molecules with other oral antidiabetic drugs (OAD) or insulin. Subjects and methods. 119 patients (59 women, 60 men) files who had started SGLT2i between 2017-2019 were examined retrospectively until 6 months after the treatment change. Patients' weight, body mass index (BMI), insulin doses, fasting blood glucose, HbA1c, lipid profile, spot urine albumin/creatinine ratio, e-GFR values, ALT, AST, uric acid levels were evaluated at baseline, 3 months and 6 months. Results. 41.2% of patients were using dapagliflozin and 58.8% were using empagliflozin. After 6 months of follow-up, HbA1c decreased from 8.27% to 7.45% (p<0.001). Daily total insulin dose decreased from 84.75 to 75.58 U/day in 3 months (p<0.004). Weight and BMI decreased significantly at 6 months. ALT, AST decreased significantly in patients using insulin (p 0.001 and 0.007), whereas spot urine microalbumin/creatinine ratio decreased at 3 and 6 months (p 0.005 and 0.020). A significant decrease was also observed in uric acid levels (p: 0.026). Conclusions. Dapagliflozin and empagliflozin have beneficial effects on decreasing glycemic parameters, weight, transaminases, uric acid and microalbuminuria in the real life environment. We also observed that SGLT2i and insulin combination is as safe and effective as combination with OAD.
Keywords: SGLT2 inhibitors; Type 2 diabetes mellitus; HbA1c; Body mass index; Weight loss; Real life experience; TYPE-2 DIABETES-MELLITUS; SERUM URIC-ACID; SGLT2 INHIBITOR; BODY-COMPOSITION; GLYCEMIC CONTROL; OUTCOMES; METAANALYSIS; REDUCTION; TRANSPORT; WEIGHT